2023
DOI: 10.1002/jbm4.10753
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐Body Metabolism and the Musculoskeletal Impacts of Targeting Activin A and Myostatin in Severe Osteogenesis Imperfecta

Catherine L. Omosule,
Dominique Joseph,
Brooke Weiler
et al.

Abstract: Mutations in the COL1A1 and COL1A2 genes, which encode type I collagen, are present in around 85%-90% of osteogenesis imperfecta (OI) patients. Because type I collagen is the principal protein composition of bones, any changes in its gene sequences or synthesis can severely affect bone structure. As a result, skeletal deformity and bone frailty are defining characteristics of OI. Homozygous oim/oim mice are utilized as models of severe progressive type III OI. Bone adapts to external forces by altering its mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In maintaining bone homeostasis, it regulates the replication and differentiation of chondrocytes, OBs and OCs, which play crucial roles in bone formation and mineralization. Furthermore, the TGF-β superfamily has a significant impact on the bone structure ( Omosule et al, 2023 ). OPG/RANKL/RANK is a major signaling pathway mediating bone resorption/bone formation.…”
Section: Tcm Flavonoids Modulate Bone Homeostasismentioning
confidence: 99%
“…In maintaining bone homeostasis, it regulates the replication and differentiation of chondrocytes, OBs and OCs, which play crucial roles in bone formation and mineralization. Furthermore, the TGF-β superfamily has a significant impact on the bone structure ( Omosule et al, 2023 ). OPG/RANKL/RANK is a major signaling pathway mediating bone resorption/bone formation.…”
Section: Tcm Flavonoids Modulate Bone Homeostasismentioning
confidence: 99%
“…It is now well known that many other organs and tissues are the source of their synthesis, including the pituitary gland, thyroid gland, bone marrow, pancreas, adrenal cortex, liver, and the reproductive organs [ 41 , 43 ]. Studies have demonstrated an involvement of activin A (Act A) in tissue inflammatory and repair responses [ 44 , 45 , 46 ]. High levels of this protein were observed in cancer patients, especially in cachectic individuals, which implies its association not only with increased inflammation but also with cachexia [ 47 ].…”
Section: Introductionmentioning
confidence: 99%